The fission yeast XMAP215 homolog Dis1p is involved in microtubule bundle organization. - Roque, H; Ward, J; Murrells, L; Brunner, D; Antony, C (Public Library of Science, 2010)
Microtubules are essential for a variety of fundamental cellular processes such as organelle positioning and control of cell shape. Schizosaccharomyces pombe is an ideal organism for studying the function and organization of microtubules into bundles in interphase cells. Using light microscopy and electron tomography we analyzed the bundle organization of interphase microtubules in S. pombe. We show that cells lacking ase1p and klp2p still contain microtubule bundles. In addition, we show that ase1p is the major determinant of inter-microtubule spacing in interphase bundles since ase1 deleted cells have an inter-microtubule spacing that differs from that observed in wild-type cells. We then identified dis1p, a XMAP215 homologue, as factor that promotes the stabilization of microtubule bundles. In wild-type cells dis1p partially co-localized with ase1p at regions of microtubule overlap. In cells deleted for ase1 and klp2, dis1p accumulated at the overlap regions of interphase microtubule bundles. In cells lacking all three proteins, both microtubule bundling and inter-microtubule spacing were further reduced, suggesting that Dis1p contributes to interphase microtubule bundling.